PHOSPHATE BINDER THERAPY AND SERUM PHOSPHATE CONTROL FOLLOWING INITIATION OF HAEMODIALYSIS - Kimberly Farrand; J Brian Copley; Jamie Heise; Moshe Fridman; Michael Keith; Arthur Silverberg (Kidney Research and Clinical Practice, 2012)
Hyperphosphataemia is associated with increased all-cause mortality in patients with chronic kidney disease (CKD), but serum phosphate (P) levels can be managed by dialysis, diet and the use of P binders. Serum P data were obtained retrospectively from a US dialysis provider for the 9 months following initiation of haemodialysis (HD) in CKD patients, who were then grouped according to the variations in their serum P. Group baseline characteristics and changes in P binder use over time were described. Variations in average monthly serum P values from months 4 to 9 were classified as either consistently in the target range (CT, 3.5–5.5 mg/dL), consistently low (CL, < 3.5 mg/dL), consistently high (CH, > 5.5 mg/dL), or varying between the low and target (LT), target and high (TH) or the low and high ranges (LH). For each group, baseline characteristics and changes in P binder use during the study were compared with CT (the reference group) to identify differences. In total, 47742 eligible patients were allocated to the six groups: CT, 7301; CL, 131; CH, 5001; LT, 6469; TH, 24469; LH, 4371. CH, TH, and LH were significantly younger than CT, with fewer comorbidities, higher incidence of elevated parathyroid hormone (PTH) and higher mean serum P; CH and TH also had higher levels of P binder use. CL and LT were older, with more comorbidities, lower PTH levels and lower levels of P binder use than CT. Overall, comparing months 8–9 with baseline (months 1–3), more patients received P binder therapy (51.7 vs 35.0%), on a larger percentage of days (50.0 vs 30.9%), but with little change in mean serum P (5.3 vs 5.2 mg/dL). By group, mean serum P increased numerically in CH (7.5 vs 6.6 mg/dL) and TH (5.6 vs 5.4 mg/dL) but decreased in other groups. Serum P can be difficult to control following initiation of HD. Patients with elevated serum P were younger, and most had higher P binder use than the reference group. Overall, binder use was lower than in other studies of HD patients. Dietary education and higher doses of the most effective P binders may be needed to improve P management.